2010
DOI: 10.1212/wnl.0b013e3181e1cec2
|View full text |Cite|
|
Sign up to set email alerts
|

A phase I/II dose-escalation trial of vitamin D3 and calcium in multiple sclerosis

Abstract: Objective: Low vitamin D status has been associated with multiple sclerosis (MS) prevalence and risk, but the therapeutic potential of vitamin D in established MS has not been explored. Our aim was to assess the tolerability of high-dose oral vitamin D and its impact on biochemical, immunologic, and clinical outcomes in patients with MS prospectively.Methods: An open-label randomized prospective controlled 52-week trial matched patients with MS for demographic and disease characteristics, with randomization to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
291
3
8

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(323 citation statements)
references
References 22 publications
(27 reference statements)
15
291
3
8
Order By: Relevance
“…Furthermore, it should be noted that the 'physiological' zone between the 75 and 200 nmol/liter 25-OH-D serum levels grossly corresponds to the serum levels observed in outdoor workers [Haddad and Chyu, 1971;Haddock et al, 1982;Barger-Lux and Heaney, 2002;Azizi et al 2012], as well as in traditionally living populations in East Africa [Luxwolda et al 2012]. This zone is far below the toxic zone, which appears to be located above the 400 nmol/liter serum level [Hathcock et al 2007;Burton et al 2010].…”
Section: Vitamin D Requirements and Insufficiencymentioning
confidence: 87%
“…Furthermore, it should be noted that the 'physiological' zone between the 75 and 200 nmol/liter 25-OH-D serum levels grossly corresponds to the serum levels observed in outdoor workers [Haddad and Chyu, 1971;Haddock et al, 1982;Barger-Lux and Heaney, 2002;Azizi et al 2012], as well as in traditionally living populations in East Africa [Luxwolda et al 2012]. This zone is far below the toxic zone, which appears to be located above the 400 nmol/liter serum level [Hathcock et al 2007;Burton et al 2010].…”
Section: Vitamin D Requirements and Insufficiencymentioning
confidence: 87%
“…Estimated linear trends were statistically significant for all markers with the exception of IP-10 for the time interval after day 8 up to day 106. Notably, two previous trials that tested vitamin D with treatment doses of up to 40,000 IU vitamin D 3 per day among patients with multiple sclerosis (MS) (57) and obese patients (58) were not able to demonstrate any significant change in a number of markers of immunity. The difference in results between these trials and our study may be explained by the follow-up time points documented, which included early response only in our trial.…”
Section: Discussionmentioning
confidence: 99%
“…Several observational studies indicate associations between vitamin D deficiency and disorders of the immune system, such as multiple sclerosis, 33 type 1 diabetes, 34 rheumatoid arthritis 35 and rejection of solid organ allografts. 36 Some studies have also shown beneficial effects of vitamin D supplementation, most notably in the prevention of type 1 diabetes, 37 and amelioration of symptoms of multiple sclerosis by treatment with high dose vitamin D. 38 However, the relevance of these findings is questioned due to the lack of prospective, randomized trials. Such trials are difficult to carry out in diseases with low incidence and slow onset, such as diabetes type 1.…”
Section: Discussionmentioning
confidence: 99%